Penarikan naskah: Efek diuretik ekstrak daun alpukat (Persea americana Mill.) pada kadar kalium dan natrium urine tikus Sprague-Dawley - Madyastuti, Rini; Nisa, Nunik Nida Choerun; Wientarsih, Ietje (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2023)
Announcement of manuscript withdrawal: The author has voluntarily submitted a request for retraction of the published manuscript. Based on these considerations, the editorial board decided to permanently withdraw this manuscript from circulation, both in print and online.